Influence of diabetes on sacubitril/valsartan titration and clinical outcomes in patients hospitalized for heart failure - Klaus K. Witte; Rolf Wachter; Michele Senni; Jan Belohlavek; Ewa Straburzynska‐Migaj; Candida Fonseca; Eva Lonn; Adele Noè; Heike Schwende; Dmytro Butylin; YannTong Chiang; Domingo Pascual‐Figal; et al. (ESC Heart Failure, 2023)
Abstract Aims Diabetes mellitus is associated with worse outcomes and lower attainment of disease‐modifying therapies in patients with heart failure with reduced ejection fraction (HFrEF). This post hoc analysis of TRANSITION compared the patterns of tolerability and uptitration of sacubitril/valsartan in patients with HFrEF stabilized after hospital admission due to acute decompensated HF depending on the presence or absence of diabetes as a co‐morbidity. Methods TRANSITION, a randomized, open‐label study compared sacubitril/valsartan initiation pre‐discharge vs. post‐discharge (up to14 days) in 991 patients hospitalized for acutely decompensated HFrEF. The impact of diabetes status on tolerability and safety was studied at 10‐week and 26‐week post‐randomization. Results Among the 991 patients analysed at baseline, 460 (46.4%) had diabetes and exhibited a higher risk profile. At 10 weeks, sacubitril/valsartan target dose (97/103 mg bid) was achieved in a similar proportion of patients in each subgroup, when initiated pre‐discharge or post‐discharge respectively [diabetes subgroup: 47% (n = 105/226) vs. 50% (n = 115/228); relative risk ratio (RRR), 0.923; P = 0.412; non‐diabetes subgroup: 45% (n = 119/267) vs. 51% (n = 133/261); RRR, 0.878; P = 0.155]. The proportions of patients achieving and maintaining either 49/51 mg or 97/103 mg bid [diabetes subgroup: 61.1% (n = 138/226) vs. 67.5% (n = 154/228); RRR, 0.909; P = 0.175; non‐diabetes subgroup: 62.9% [n = 168/267] vs 69.3% [n = 181/261]; RRR, 0.906; P = 0.118] or any dose for ≥2 weeks leading to Week 10 [diabetes subgroup: 85% (n = 192/226) vs. 88.2% (n = 201/228); RRR, 0.966; P = 0.356; non‐diabetes subgroup: 86.9% (n = 232/267) vs. 90.8% (n = 237/261); RRR, 0.963; P = 0.215] were also similar in each subgroup, when initiated pre‐discharge or post‐discharge, respectively. At 10 weeks, hypotension and renal dysfunction rates were similar, although hyperkalaemia was higher among patients with diabetes (15.9% vs. 9.5%). The rate of permanent discontinuation due to adverse events was similar in the diabetes and non‐diabetes subgroups at 10 weeks, respectively: pre‐discharge (7.5% vs. 7.1%) or post‐discharge (5.7% vs. 4.2%). Similar patterns of uptitration and tolerability were observed at 26 weeks. Cardiac biomarkers including NT‐proBNP (P < 0.005) and hs‐TnT (P < 0.005) reduced significantly from baseline levels in both subgroups at Weeks 4 and 10; however, the response was greater among patients without diabetes. Mortality (diabetes vs. non‐diabetes subgroups: 3.3% vs 4.0%; P = 0.438) and HF rehospitalization (diabetes vs. non‐diabetes subgroups: 36.3% vs. 33.0%; P = 0.295) did not differ between the groups at 26 weeks. Conclusions Despite a higher risk profile among patients with diabetes, sacubitril/valsartan initiation either before or shortly after discharge in hospitalized patients with HFrEF resulted in comparable rates of dose up‐titration and tolerability as in those without diabetes.